Repellent effect and insecticidal activities of Bridelia ferruginea, Blighia sapida, and Khaya senegalensis leaves powders and extracts against Dinoderus porcellus in infested dried yam chips - Loko, L.Y.; Alagbe, O.; Dannou, E.A.; Datinon, B.; Orobiyi, A.; Thomas-Odjo, A.A.; Dansi, A.; Tamò, Manuele (Hindawi Limited, 2017)
Dinoderus porcellus is considered as the most important pest of stored yam chips and compounds extracted from plants can be used for its control. The present study aimed to test the insecticidal and repellent activities of powders and extracts of leaves of Bridelia ferruginea, Blighia sapida, and Khaya senegalensis against D. porcellus. The efficacy of plant powders was compared with the synthetic pesticide Antouka (Permethrin 3 g/kg + pirimiphos 16 g/kg). The results of the experiment revealed that all plant powders were effective as repellents. Antouka was more effective as insecticidal than the plant powders and minimal weight loss was observed with B. sapida at 2%. Among treatments, propanol extract of K. senegalensis at 5% was found to elicit the highest repellent effect on D. porcellus. The LC50 results revealed that the acetone extract of K. senegalensis is the most toxic (0.29 μL/insect) to the pest, while the propanol extract of B. ferruginea at 5% exhibited strong fumigant toxicity against D. porcellus, with 88.89% of pest mortality at 160 μL/L air. The findings from the current work proved that plant powders and extracts of the three plants are sources of botanical insecticides which may be used in the integrated management of D. porcellus.